Risk factors for Shiga toxin-producing Escherichia coli infections in preadolescent schoolchildren in Buenos Aires, Argentina - Bentancor, Adriana Beatriz; Ameal, Luis A; Calviño, María F; Martinez, María C; Miccio, Luciano; Degregorio, Osvaldo J (The Journal of Infection in Developing Countries, 2011)
Introduction: Shiga toxin-producing Escherichia coli (STEC) infections are the leading cause of hemolytic uremic syndrome (HUS). STEC is the most common cause of acute kidney disease, responsible for 20% of renal transplants in Argentina. Methodology: In 2007, an epidemiological survey was conducted among 883 students from the fifth and sixth years of elementary education in the public schools of San Martin City, Buenos Aires, Argentina. Degree of exposure to the known risk factors previously detected in the region as primary causes of STEC infections was evaluated. Risk factors assessed included consumption of hamburgers, poor personal hygiene, and exposure to various types of drinking and recreational water. The study was designed to evaluate exposure to risk factors for STEC infections among different socioeconomic groups. Results: Ninety-five percent of children surveyed reported consumption of hamburgers. Most of these hamburgers were precooked. Children of high and medium strata attended private swimming-pools, while children from the low stratum attended public pools. Only 30.2% of students washed their hands after going to the toilet and only 43.5% reported hand-washing before eating. Conclusions: Students demonstrated high levels of exposure to identified risk factors for STEC infections. Reduction of these risks will require cultural changes aimed at decreasing morbidity caused by food-borne infections. Institutional framework must provide the necessary resources to implement these changes and emphasize the importance of good personal hygiene. Health education must be implemented to increase food safety awareness of the consumers.